AGRICULTURE AS A TOOL FOR FOOD SECURITY IN NIGERIA - Anthony Azor Abu,; Maliki Abu,; Akintunde Abiodun Ajulo,; Franklyn Imochi Oshoke,; Oladimeji Joshua Ajiyo, (International Journal of Innovations in Engineering Research and Technology, 2021)
This study is on agriculture as a tool for food security in Nigeria. The specific objective of the study is to examine the significant impact of government expenditure on agriculture (GEA), bank loans and advances to cash crops farmers, livestock farmers, fishery farmers, food crops farmers on agricultural output /food security in Nigeria. The study uses the ex-pecto research design and the ordinary least square (OLS) regression analysis as a method of data analysis. The findings reveals that shows that government expenditure on agriculture (GEA) and Bank loans and advance to cash crops production (LCC) has significant economic impact in agricultural food security, while shows that LFISH, LLIVS and LFC has no significant economic impact on agricultural output/ food security in Nigeria. Among other recommendations, it is recommended that Nigerian government should provide needed financial support and monitoring teams to National Agricultural Systems, Nigerian agricultural and research institutes in order to deliver their core mandate on the farming of livestock, and food crops to have significant impact on agricultural output/ food security in Nigeria.